The role of the endolysosomal pathway in α-synuclein pathogenesis in Parkinson’s disease - Smith, Jessica K.; Mellick, George D.; Sykes, Alex M. (Frontiers in Cellular Neuroscience, 2023)
Parkinson’s disease (PD) is a chronic neurodegenerative disease that is characterised by a loss of dopaminergic neurons in the substantia nigra pars compacta of the midbrain. Extensive studies into genetic and cellular models of PD implicate protein trafficking as a prominent contributor to the death of these dopaminergic neurons. Considerable evidence also suggests the involvement of α-synuclein as a central component of the characteristic cell death in PD and it is a major structural constituent of proteinaceous inclusion bodies (Lewy bodies; LB). α-synuclein research has been a vital part of PD research in recent years, with newly discovered evidence suggesting that α-synuclein can propagate through the brain via prion-like mechanisms. Healthy cells can internalise toxic α-synuclein species and seed endogenous α-synuclein to form large, pathogenic aggregates and form LBs. A better understanding of how α-synuclein can propagate, enter and be cleared from the cell is vital for therapeutic strategies.